Pengaruh Penerapan Metode Jarimatika terhadap Hasil Belajar Matematika pada Materi Operasi Hitung di Kelas III - Kamila Raihanah, Fairuz; Supriyanto Manurung, Alberth (Education Achievement: Journal of Science and Research, 2025)
This research is based on the low average mathematics learning outcomes of class III students at SDN Sriamur 04, this can be seen when the class teacher only uses lecture and demonstration methods with stick pieces which take a long time to calculate. Apart from that, it was also seen that some students had difficulty memorizing multiplications of 6 and above. The purpose of this research is to find out whether the Jarimatics method influences the mathematics learning outcomes of students in class III at SDN Sriamur 04 on multiplication arithmetic operations. This research uses a quantitative approach using the form of Pre-Experimental Design, One-Group Pretest-Posttest Design. In this study, the population was all class III students at SDN Sriamur 04, Bekasi district with a total of 55 students. The research sample was class III A students, totaling 28 students. The average pretest result was 51.00. After the pretest, treatment was given in the form of applying the Jarimatika method to improve mathematics learning outcomes in multiplication calculation operations. During the treatment, there was an improvement which was visible from the posttest results, which obtained an average of 79.57. To test significance using the paired sample t-test, the sig value is known. (2-tailed) of 0.000. According to the basis for decision making in the paired sample t-test, the sig. (2-tailed) < 0.05 or 0.000 < 0.05. This means that the hypothesis H0 is rejected and Ha is accepted because there is a significant difference between the pretest and posttest learning outcomes. So it can be concluded that there is an influence of the application of the Jarimatics method on mathematics learning outcomes in class III multiplication calculation operations at SDN Sriamur 04.